Asean And Biosecurity Law: Experience And Dilemmas Of Regional Integration In Southeast Asia - Noor Dzuhaidah Osman; N.Z.Chow Jen-T’chiang (Institute of China and Contemporary Asia of the Ru, 2024)
A plethora of legal instruments and agencies currently control and enforce various biosafety, biosecurity and public health issues. This article proposes a regional ASEAN model of biosecurity regulations that include viruses, diseases, and biological agents as potentially dangerous organisms to protect human health, animals, plants and the environment. This work analyses and defines alternative methods of biosecurity governance through doctrinal legal research. This biosecurity paradigm will enable these bodies and organisations to better integrate with the various instruments charged with controlling biosafety, biosecurity, pandemics, and bioweapons. All actors involved in regulating should have some common ground or perhaps a new different body to coordinate all the various threats in the future. It is proposed to develop an integrated ASEAN approach to biosecurity, covering biosafety, pandemic and biological weapons issues. Despite pandemics and other potential threats, a common standard protocol in ASEAN region will allow unrestricted movement of people, trade, tourism, and other services.